EARLY ISLAMIC CRUDE HANDMADE WARE: NEW INSIGHTS ON THE TYPOLOGY, CHRONOLOGY AND PROVENANCE OF A SOUTHERN LEVANTINE HANDMADE POTTERY. Issue 3 (7th July 2022) - Taxel, Itamar; Shamir, Orit; Waiman‐Barak, Paula; Ondricek, Willie; Ayalon, Etan
Summary: This study presents new evidence about a class of Early Islamic ceramics that have been largely overlooked; namely, crude handmade ware, sometimes previously referred to as 'Negebite' Ware, typical of the southern portions of what is now modern‐day Israel and Jordan. A large array of handmade vessels retrieved in excavations of an Early Islamic settlement in the Yotvata oasis of the 'Arabah Valley, Israel and comparative material from neighbouring sites, provide a basis for new perceptions. These consist of a typo‐chronology of Early Islamic crude handmade wares, clarification of previously unrecognized production techniques (including ones based on evidence from textile impressions), and the results of initial petrographic analysis. We also explore chronological and cultural links between this family of ceramics and other endemic Islamic‐period handmade wares that are known from the region.